EFEKTIVITAS SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) DALAM IMPLEMENTASI UNDANG-UNDANG NOMOR 24 TAHUN 2013 DI KUA KECAMATAN MEJOBO KUDUS - Fuad Riyadi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Manajeman Marriage Information System (SIMKAH) is a aplicationprogam based on windows computer that is useful for collectingmarriage data from all Religious Affairs Offices (KUA) in the Republicof Indonesia online and offline, the data will be stored safely at thelocal KUA, in the Regency in Provincial Regional Offices and inIslamic Community Development. These data are useful for makingvarious analyzes and reports according to various needs. The SIMKAHaims to help implement Law no 24 of 2013 Concerning Amendments toLaw no 23 of 2006 Concerning Population Administration. Althoughthis effort has not gone well